Public Reception Toward Ms Glow For Men Skincare Brand Ambassador Babe Cabiita And Marshel Widianto Ads Edition - Triani, Rori; Narti , Sri; Octaviani , Vethy (Multidisciplinary Journals, 2024)
This research is entitled public reception toward Ms. Glow for Men skincare Brand Ambassador Babe Cabiita and Marshel Widianto Ads Edition. The reason of the researcher made the MS Glow for men skincare brand ambassador Babe Cabiita and Marshel Widianto Ads edition as the object of research, is because this advertisement uses a Brand Ambassador who does not have a masculinity side as usually displayed by the media. This study aims to determine the public reception on Ms. Glow for Men skincare Brand Ambassador Babe Cabiita and Marshel Widianto Ads Edition. This research is a type of qualitative research with data analysis techniques using the Reception theory of Stuart Hall. Stuart Hall explained that the audience's meaning of a message in the media can be seen from three points of view, namely Dominant Hegemonic Reading, Negotiated Reading and Oppositional Hegemonic Reading. In this study, researchers also conducted Pierce Semiotics Analysis on 6 out of 10 scenes in Ms. Glow for Men skincare Brand Ambassador Babe Cabiita and Marshel Widianto Ads Edition to make it easier for researchers to find out the meaning of the advertisement. The results of the research that the researchers conducted on 4 informants only produced 2 categories of audiences, namely the position of Dominant Hegemonic Reading and Negotiated Reading. The Dominant Hegemonic Reading position is a position where the audience fully accepts the meaning contained in the advertisement, there are 2 informants who are in this position, while the Negotiated Reading position is a position where the audience accepts but modifies the message in the advertisement, there are 2 informants who are in this position.